2019
DOI: 10.17221/21/2018-pps
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium culmorum Tri genes and barley Hvugt13248 gene transcription in infected barley cultivars

Abstract: The transcription activities of genes somehow associated with the mycotoxin deoxynivalenol (DON) biosynthesis, namely Fusarium Tri genes, and the barley gene coding for UDP-glycosyltransferase (HvUGT13248) on different genetic backgrounds were compared. Determining the amount of the pathogen DNA was used as a useful tool for evaluating the infestation of barley cultivars. Amounts of the pathogen DNA differed in six barley cultivars infected by F. culmorum. Transcription of HvUGT13248 was related to DON content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Faltusova et al. (2019) observed that UDP‐glycosyltransferase encoded by HvUGT13248 gene in barley can rapidly and efficiently convert DON into D3G rapidly and efficiently, and its transcriptional activity was correlated with DON content in the samples. Moreover, UDP‐glycosyltransferase HvUGT13248 can transform DON to the nontoxic DON‐3‐ O ‐beta‐ d ‐glucoside, which expressed in transgenic wheat and yeast can result in high levels of type II resistance to DON‐producing F. graminearum strains (Li et al., 2017).…”
Section: Don Biological Detoxification Methods and Nutritional Mitiga...mentioning
confidence: 99%
“…Faltusova et al. (2019) observed that UDP‐glycosyltransferase encoded by HvUGT13248 gene in barley can rapidly and efficiently convert DON into D3G rapidly and efficiently, and its transcriptional activity was correlated with DON content in the samples. Moreover, UDP‐glycosyltransferase HvUGT13248 can transform DON to the nontoxic DON‐3‐ O ‐beta‐ d ‐glucoside, which expressed in transgenic wheat and yeast can result in high levels of type II resistance to DON‐producing F. graminearum strains (Li et al., 2017).…”
Section: Don Biological Detoxification Methods and Nutritional Mitiga...mentioning
confidence: 99%
“…begins with the cyclization of farnesyl pyrophosphate and is catalyzed by terpene cyclase trichodiene synthase (Tri5) that is encoded by the ( Tri5 ) gene [ 11 ]. The Tri6 gene is one of the genes regulating the expression of other Tri genes for the biosynthesis of trichothecenes [ 12 ]. EF1A is involved in the protein translation machinery of eukaryotic cells and has been shown to be a powerful tool for distinguishing related Fusarium species [ 13 ].…”
Section: Introductionmentioning
confidence: 99%